The sector coupling concept: A critical review - Ramsebner, Jasmine; Haas, Reinhard; Ajanovic, Amela; Wietschel, Martin (Wiley interdisciplinary reviews. Energy and environment, 2021)
Pursued climate goals require reduced greenhouse gas emissions by substituting fossil fuels with energy from renewable sources in all energy‐consuming processes. On a large‐scale, this can mainly be achieved through electricity from wind and sun, which are subject to intermittency. To efficiently integrate this variable energy, a coupling of the power sector to the residential, transport, industry, and commercial/trade sector is often promoted, called sector coupling (SC). Nevertheless, our literature review indicates that SC is frequently misinterpreted and its scope varies among available research, from exclusively considering the use of excess renewable electricity to a rather holistic view of integrated energy systems, including excess heat or even biomass sources. The core objective of this article is to provide a thorough understanding of the SC concept through an analysis of its origin and its main purpose, as described in the current literature. We provide a structured categorization of SC, derived from our findings, and critically discuss its remaining challenges as well as its value for renewable energy systems. We find that SC is rooted in the increasing use of variable renewable energy sources, and its main assets are the flexibility it provides for renewable energy systems, decarbonization potential for fossil‐fuel‐based end‐consumption sectors, and consequently, reduced dependency on oil and gas extracting countries. However, the enabling technologies face great challenges in their economic feasibility because of the uncertain future development of competing solutions. This article is categorized under: Energy Systems Economics > Economics and Policy Energy Systems Economics > Systems and Infrastructure Technical sector coupling pathways: Using renewable electricity in all end‐consumption sectors.